On a model of the nonlinear torsional vibration with variable generalized masses - Khang, Nguyen Van; Son, Tran Dinh (Vietnam Journal of Mechanics, 1992)
In this paper the establishment of the parametric vibration differential equations for a model of the nonlinear torsional vibration with variable generalized masses considered.